Highly Flexible and Transparent Multilayer MoS2 Transistors with Graphene Electrodes. Issue 19 (18th February 2013) - Yoon, Jongwon; Park, Woojin; Bae, Ga‐Yeong; Kim, Yonghun; Jang, Hun Soo; Hyun, Yujun; Lim, Sung Kwan; Kahng, Yung Ho; Hong, Woong‐Ki; Lee, Byoung Hun; Ko, Heung Cho
Abstract A highly flexible and transparent transistor is developed based on an exfoliated MoS2 channel and CVD‐grown graphene source/drain electrodes. Introducing the 2D nanomaterials provides a high mechanical flexibility, optical transmittance (∼74%), and current on/off ratio (>104) with an average field effect mobility of ∼4.7 cm2 V−1 s−1, all of which cannot be achieved by other transistors consisting of a MoS2 active channel/metal electrodes or graphene channel/graphene electrodes. In particular, a low Schottky barrier (∼22 meV) forms at the MoS2/graphene interface, which is comparable to the MoS2/metal interface. The high stability in electronic performance of the devices upon bending up to ±2.2 mm in compressive and tensile modes, and the ability to recover electrical properties after degradation upon annealing, reveal the efficacy of using 2D materials for creating highly flexible and transparent devices.